Empowering women at the higher institutional level: analysis of business education and leadership training program - Khalid, Summra; Dan, Wang; Sohail, Amir; Raza, Wahid; Khalid, Bushra; Ur-Rehman, Ahmad (Business, Management and Economics Engineering, 2021)
Purpose – The research study aims to assess the women’s Business education and leadership training program at a higher institutional level in order to examine how the program impacts and contributes to women’s empowerment. Further, this research sought to explore women’s leadership training aspect that has not explicitly elucidated. Besides, this study looks upon women’s self-perception by empowering them with skills and leadership capabilities to change hard-core gender stereotypes in society.Research methodology – The sample size comprised of 82 enrolled female students in the training program. The qualitative statistics (i.e., three focus groups) evaluated with the Kirkpatrick model. The Wilcoxon signed-rank test was applied to compare pre-and post-training quantitative data (i.e., questionnaire). Effect size is measured to check the effectiveness of the training program.Findings – The post-training evaluation revealed higher scores in knowledge, tools, and leadership skills. The training program encouraged women to bring change in self-perception and gain confidence for transformative changes in society. Findings support the effectiveness of leadership education and training programs.Research limitations – This research conducted in a Pakistani patriarchal cultural context and one region of Pakistan (Punjab). Hence the results are carefully generalised. The long term outcomes of this leadership training program and women’s performance in the job market are not studied.Practical implications – Findings suggest that a training program positively affects women’s learning, knowledge, and behaviour. Training programs empower women with practical tools for self and business development. The program encouraged women to gain better insight into work-life challenges and enhance personal competencies to gain equal rights.Originality/Value – This research will significantly contribute to the relatively scarce literature on the effectiveness of women’s business education and leadership training programs at a higher institutional level in the Pakistani context for women empowerment.